Ordinance no. 22, § 1: An Ordinance Relating to Concealed Weapons and Providing Penalty for Carrying Same, in THE HARLOWTON NEWS, Jun. 18, 1909, at 3 - (:unkn) unknown (My University, 1909)
No person in the town of Harlowton shall wear under his or her clothes or concealed on or about their person, any pistol or revolver, except by special permission from the Mayor; nor shall any person wear under his or her clothes or concealed on or about their person, any slingshot, cross knuckles of lead, brass or other metal, or any bowie-knife, razor, billy, dirk, dirk-knife or daggor, or any knife resembling a bowie-knife, or any other dangerous or deadly weapon
Keywords: CARRY - CONCEALED